Penerapan Balanced Scorecard untuk Pengukuran Kinerja Perguruan Tinggi Islam - Maryani, Ay; Nur Wachidah Yulianti (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2023)
Abstract: Application of the Balanced Scorecard for the Performace Measurement of Islamic Higher Education Purpose : This study aims to analyze the application of the Balanced Scorecard in measuring the performance of Islamic higher education. Methode : Qualitative method was employed, with a case study approach. Results : The results showed that the balanced scorecard was able to measure the performance of Islamic higher education from financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Novelty: Implementation of the Balanced Scorecard with the aspect of educational fees for the single tuition scheme. Contribution: This article provides alternative solution for Islamic higher education in evaluating the determination of education fees and their services, to ensure that students may obtain justice in education. Abstrak: Penerapan Balanced Scorecard untuk Pengukuran Kinerja Perguruan Tinggi Islam Tujuan: Penelitian ini bertujuan untuk menganalisis penerapan Balanced Scorecard dalam mengukur kinerja perguruan tinggi Islam. Metode: Metode yang digunakan adalah kualitatif, dengan pendekatan studi kasus. Hasil: Hasil penelitian menunjukkan bahwa Balanced Scorecard mampu mengukur kinerja perguruan tinggi Islam dari perspektif keuangan, perspektif pelanggan, perspektif proses bisnis internal, dan perspektif pembelajaran dan pertumbuhan. Kebaruan: Implementasi Balanced Scorecard dengan aspek biaya pendidikan untuk skema biaya kuliah tunggal. Kontribusi: Artikel ini memberikan solusi alternatif bagi perguruan tinggi Islam dalam mengevaluasi penetapan biaya pendidikan dan layanannya, sehingga mahasiswa dapat memperoleh keadilan dalam pendidikan.